Criteria influencing pedestrian-friendliness of first/last mile transit journey using Analytical Network Process (ANP) group judgement - Nabilah Naharudin; Mohd Sanusi S Ahamad; Ahmad Farhan Mohd Sadullah (Penerbit Universiti Kebangsaan Malaysia, 2019)
The pedestrian-friendliness of the first/last mile (FLM) transit journey is one of the keys in influencing the quality of transit services. The demands of transit riders are increasing as they have started to ask for more than just accessibility which includes a good walking environment to access the service. Most local governments are aware of this as many of them have the guidelines in planning for a walkable transit services. However, they need to prioritise the criteria influencing pedestrian-friendliness accordingly. This paper proposes a framework for evaluating the priorities of criteria influencing pedestrian-friendliness by using Analytical Network Process (ANP) which relies on group judgement from experts who have wide knowledge and experience within the scope of the study. It can be conducted in six stages which are (1) determining criteria influencing pedestrian-friendliness (2) developing ANP model of the criteria and their dependencies, (3) obtaining experts judgement, (4) aggregating the criteria’s priorities, (5) deriving group judgement of the criteria’s priorities, and (6) ranking the criteria accordingly. In the end, this study will suggest the priorities for criteria influencing pedestrian-friendliness which can be used as reference in planning for walking environment to access transit services. This study highlighted nineteen criteria that could be used in representing the pedestrian-friendliness of FLM. Based on the analysis, it is suggested that from the nineteen criteria, the presence of signage showing direction is the most important criterion followed by roofed walkway, convenience in term of walking time, access to public parks and presence of traffic lights.